HAND HYGIENE KNOWLEDGE, PRACTICE AND FACILITIES UTILIZATION OF PUPILS IN BATANGAS CITY, PHILIPPINES: BASIS FOR PROPOSED HAND HYGIENE ACTIVITIES - Asilo, Mardes M; Berberabe, Jennifer; Ramos, Aquilina De (LIFE: International Journal of Health and Life-Sciences, 2018)
This study assessed the hand hygiene knowledge, practice and facilities utilization of pupils in Batangas City, Philippines during academic year 2016-2017. Using a self-structured questionnaire, the researchers selected one thousand one hundred eighteen (1,118) pupils as participants in this research. They analyzed the responses of the pupils through the use of frequency counts, weighted mean, t-test and Analysis of Variance (ANOVA) to determine the difference of responses among grade levels and school type. The study found out school type had the most influence on pupils’ learning concepts about hand hygiene as well as its implementation and the provision of adequate supplies & facilities. Public school pupils showed higher scores in hand hygiene knowledge, practice and facilities utilization as well as greater interest on the proposed hand hygiene activities. These included, among others, conduct of health teaching on proper hand hygiene technique with disease education and preparation of individual hygiene kit for pupils. On the other hand, grade level was determined not to have significant difference on the pupils’ know-how in hand cleansing. This is because regardless of the pupils grade level their knowledge, practice and facilities utilization including interest on the suggested hand hygiene health activities remain the same. It is further recommended that school administrators take action on the pupils’ interest regarding hand hygiene health activities proposed in the study.